Glycoproteins II - Montreuil, Jean, 1920-2010; Vliegenthart, J. F. G.; Schachter, H. (Harry) (New comprehensive biochemistry, 1997)
Part II of this excellent work covers proteoglycans and mucins and deals with many more examples of glycoprotein function. It also covers glycoproteins from four more species (slime mold, snails, fish, batracians). The content of the volume is very comprehensive in that most contributors are focussed on discussing, in depth, the wealth of most recent advances in their field, referring to previous reviews of older work for background information. This method effectively produces a very wide subject coverage in a smaller number of chapters/volumes.